2022
DOI: 10.3390/cells11193073
|View full text |Cite
|
Sign up to set email alerts
|

The Immune and Regenerative Response to Burn Injury

Abstract: Burn are diverse and complex injuries that not only have local effects but also serious systemic consequences through severe and prolonged inflammatory response. They are caused by heat, electricity, friction, chemicals, or radiation and are commonly divided into superficial, superficial partial-, deep partial- and full-thickness injuries. The severity of the burn depends mainly on the size and depth of the injury but also on location, age, and underlying systemic diseases. A prolonged and strong immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 159 publications
1
32
0
Order By: Relevance
“…The control (healthy) group showed significantly higher levels of T, NK, and B primitive cells compared with the burn group. The burned individuals showed significantly higher levels of monocytes, macrophages, mast cells, neutrophils, plasma cells, and T cells gamma delta, which was consistent with our cognition (Figure 8A) (22).…”
Section: Immune Infiltration Landscape Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The control (healthy) group showed significantly higher levels of T, NK, and B primitive cells compared with the burn group. The burned individuals showed significantly higher levels of monocytes, macrophages, mast cells, neutrophils, plasma cells, and T cells gamma delta, which was consistent with our cognition (Figure 8A) (22).…”
Section: Immune Infiltration Landscape Analysissupporting
confidence: 91%
“…Notably, mast cells are not only present in the early stages of the immune system response to burns. Meanwhile, the role of B cells may be downregulated after thermal injury ( 22 ). In our study, these phenomena were well confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Large burns are very relevant public health problems causing massive tissue destruction and dramatic pathophysiologic effects on the burnt patient 1 . As an intact healthy skin is necessary to protect the internal tissues, a proper skin barrier is essential for patient survival 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The morphological aspects of the wound process are the focus of attention for various researchers. Burn wounds are of special significance compared to other skin injuries due to both the specificity of the wound process and the long-term restoration of skin integrity [ 1 , 2 ]. The restoration of the skin as an organ after thermal alteration is directly related to the state of the extracellular matrix of the dermis, including the amphora and fibrous components.…”
Section: Introductionmentioning
confidence: 99%